2013
DOI: 10.21273/hortsci.48.12.1463
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Net Development as a Barrier to Moisture Loss in Netted Melon Fruit (Cucumis melo L.)

Abstract: The transpiration rate of cuticular membrane and fissures that comprise the netting on fruits of three netted melon cultivars, Life, Andesu, and Gurandoru, were measured during fruit development. Fissures in the equatorial region first developed vertically, then became interconnected by horizontal fissures as the fruit developed. Some cracks remained along the net, even at the fruit ripening stage, regardless of cultivar. Both lignified and suberized cell wall layers in the net tissues of the cultivar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…However, the differences in the mapping results between the two trials depict significant genotype-by-trial interactions for ND and NW confirmed by the combined analysis of variance mentioned earlier. This suggests ND and NW are at least partly affected by environmental factors similar results were reported in previous studies (Keren-Keiserman et al 2004 ; Puthmee et al 2013 ). Two QTLs (i.e., qNW2 and qNW7 ) were identified in both trials, indicating relatively stable ones which would be useful for MAS in the future.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, the differences in the mapping results between the two trials depict significant genotype-by-trial interactions for ND and NW confirmed by the combined analysis of variance mentioned earlier. This suggests ND and NW are at least partly affected by environmental factors similar results were reported in previous studies (Keren-Keiserman et al 2004 ; Puthmee et al 2013 ). Two QTLs (i.e., qNW2 and qNW7 ) were identified in both trials, indicating relatively stable ones which would be useful for MAS in the future.…”
Section: Discussionsupporting
confidence: 89%
“…Mapping of QTLs for netting width of fruit rind was unique in this study. Netting on melon surface, a wound-healing network pattern, has been reported results from a series of histological and biochemical processes (Keren-Keiserman et al 2004 ; Puthmee et al 2013 ). Fruit netting was scored by both netting density and netting width in which the same QTLs in LG 2, 4, 6, and 7 were identified for both traits.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of lignosuberized periderm tissue holds agronomical and physiological significance as it maintains the integrity of the skin surface, and protects the growing and expanding fruit under skin-failure circumstances [ 4 ]. Previous studies established that reticulation impacts melon fruit skin firmness and elasticity [ 5 , 6 , 7 ], maintains the turgor pressure and waterproofing volume of hypodermal cells lying beneath the skin layer [ 8 ], and delivers enhanced tolerance against mechanical injury [ 9 ]. Similarly, newly-formed phellem cells that build the russeted coating in apple fruit were shown to replace damaged epidermis cells, thereby preserving normal water loss during fruit development and post-harvest [ 2 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, peroxidase activity was associated with processes of suberization and lignification occurring at the reticulated surface (Keren-Keiserman et al, 2004b). Differences in the structure of the skin surface, smooth or reticulated, impact fruit physiology and development, including firmness and elasticity (Rose et al, 1998;Dos-Santos et al, 2011;Puthmee et al, 2013), waterproofing capacity, and turgor pressure of hypodermal tissues (Saladié et al, 2007). They further confer tolerance against mechanical damage (Keren-Keiserman et al, 2004a).…”
mentioning
confidence: 99%